Pulmonary effects of ozone therapy at different doses combined with antibioticotherapy in experimental sepsis model - Kapicibaşi,Hasan Oğuz (2020)
Abstract Purpose This experimental sepsis model created with Escherichia coli aimed to investigate the histopathological effects of two different doses of ozone combined with antibiotherapy on lung tissue. Methods Rats were divided into 5 groups. Then sepsis was induced intraperitoneally in the first 4 groups. The 1st group was treated with cefepime, the 2nd and 3rd groups were treated with cefepime combined with ozone at a dose of 0.6 mg/kg and 1.1 mg/kg. Lung tissue sections were stained with hematoxylin-eosin and assessed under light microscope and scored between 0-4 in terms of histopathological findings. Results In the comparisons between Group 1 and Group 4 in terms of cellular damage (p=0.030), inflammation (p=0.000) and overall score (p=0.007), statistically significant positive effects were observed in favor of Group 1. In the comparisons of Groups 2 and 3 with Group 4, only positive effects were observed in terms of inflammation (p=0.020, p=0.012, respectively). Conclusion Although negative histopathological effects of ozone on tissue injury were detected, it was noteworthy that the increase in the ozone dose reduced the number of damaged parameters.